Repensando o lugar da representação, da transmissão e da experiência no ensino da Filosofia - Garcia, Amanda Veloso [UNESP]; Gelamo, Rodrigo Pelloso [UNESP] (My University, 2012)
The question that we develop in this study can be proposed as follows: can knowledge be transmitted in a representational way through an explanation in such a way that the one who is learning does not have an experience itself of what he is learning? Grounded on Hume, Deleuze, Rancière and Gallo, we aim to show that only the experience with the object can promote effective learning, for violating the thought to search by itself for its meaning and for its own understanding, and not for the mere repetition of contents that have been shared and taken as important, as we have seen in schools.

Será que o conhecimento pode ser transmitido de forma representacional, por meio de uma explicação, sem que aquele que aprende faça uma experiência por si só daquilo que aprende? Este artigo, amparando-se no pensamento de Hume, Deleuze, Rancière e Gallo, pretende mostrar que somente a experiência com o objeto pode promover a aprendizagem efetiva, violentando o pensamento para que este busque por si só seu sentido e forme sua própria apreensão.
Keywords: Ensino de Filosofia; experiência; representação